Socializing in an Infectious World: The Role of Parasites in Social Evolution of a Unique Rodent Family - Lutermann, Heike (Frontiers in Ecology and Evolution, 2022)
Transmission of parasites between hosts is facilitated by close contact of hosts. Consequently, parasites have been proposed as an important constraint to the evolution of sociality accounting for its rarity. Despite the presumed costs associated with parasitism, the majority of species of African mole-rats (family: Bathyergidae) are social. In fact, only the extremes of sociality (i.e. solitary and singular breeding) are represented in this subterranean rodent family. But how did bathyergids overcome the costs of parasitism? Parasite burden is a function of the exposure and susceptibility of a host to parasites. In this review I explore how living in sealed burrow systems and the group defenses that can be employed by closely related group members can effectively reduce the exposure and susceptibility of social bathyergids to parasites. Evidence suggests that this can be achieved largely by investment in cheap and flexible behavioral rather than physiological defense mechanisms. This also shifts the selection pressure for parasites on successful transmission between group members rather than between groups. In turn, this constrains the evolution of virulence and favors socially-transmitted parasites (e.g. mites and lice) further reducing the costs of parasitism for social Bathyergidae. I conclude by highlighting directions for future research to evaluate the mechanisms proposed and to consider parasites as facilitators of social evolution not only in this rodent family.